Role of Vitamin D Receptor Gene Polymorphism with Steroid Receptors in Breast Cancer: an Update: Life Sciences- Biochemistry - Kumar Dogra, Ashok; Prakash, Pranav; Gupta, Sanjay; Gupta, Meenu; Prakash, Archana; Bashir, Haamid Bashir (International Journal of Life Science and Pharma Research, 2022)
This review touches on new insights into the possible role of Vitamin D receptors genetic polymorphisms, and steroid receptors in the patients diagnosed with breast cancer. This is the most common cancer in women; further, it creates diverse illnesses among the diseased patients, and the prognosis is linked with the different subtypes present in the hormone receptors. Most of the review studies focus on the epidemiology of the disease. However, fewer studies are done on the genes polymorphism prognosis, which plays a more significant role in the prognosis and diagnosis of breast cancer, so by proper screening at the genetic level as early, can predict the disease in females which will help the clinicians in better management of the disease. Hence the burden of disease and its ill effects can be reduced in the patient care system. Thus the Vitamin D levels in the serum and the vitamin D receptors (VDR) transcriptionally controls its target genes in the cell proliferation, differentiation, and death pathways in a ligand-dependent manner, providing protection against cancer growth and progression. Also, there are strong relationships between VDR polymorphisms and steroid hormone (estrogen, progesterone, and androgen) receptors, which will help in the prognosis and diagnosis of breast cancer disease. We recommend early screening of these receptors using advanced molecular biology techniques like Real-time Polymerase chain reaction, Chemiluminescence, Western blotting which will help to detect the genotyping of these genes at the earlier stages and are non-invasive, patient-friendly, reliable, and accurate. Vitamin D receptor gene polymorphism and steroid receptors themselves can act as early predictive biomarkers for many studies that are to be warranted further in the different ethnic populations with large sample sizes.